Multiplex tests to identify gastrointestinal bacteria, viruses and parasites in people with suspected infectious gastroenteritis: a systematic review and economic analysis. - Freeman, Karoline (Health Technol Assess, 2017)
BACKGROUND: Gastroenteritis is a common, transient disorder usually caused by infection and characterised by the acute onset of diarrhoea. Multiplex gastrointestinal pathogen panel (GPP) tests simultaneously identify common bacterial, viral and parasitic pathogens using molecular testing. By providing test results more rapidly than conventional testing methods, GPP tests might positively influence the treatment and management of patients presenting in hospital or in the community. OBJECTIVE: To systematically review the evidence for GPP tests [xTAG(®) (Luminex, Toronto, ON, Canada), FilmArray (BioFire Diagnostics, Salt Lake City, UT, USA) and Faecal Pathogens B (AusDiagnostics, Beaconsfield, NSW, Australia)] and to develop a de novo economic model to compare the cost-effectiveness of GPP tests with conventional testing in England and Wales. DATA SOURCES: Multiple electronic databases including MEDLINE, EMBASE, Web of Science and the Cochrane Database were searched from inception to January 2016 (with supplementary searches of other online resources). REVIEW METHODS: Eligible studies included patients with acute diarrhoea; comparing GPP tests with standard microbiology techniques; and patient, management, test accuracy or cost-effectiveness outcomes. Quality assessment of eligible studies used tailored Quality Assessment of Diagnostic Accuracy Studies-2, Consolidated Health Economic Evaluation Reporting Standards and Philips checklists. The meta-analysis included positive and negative agreement estimated for each pathogen. A de novo decision tree model compared patients managed with GPP testing or comparable coverage with patients managed using conventional tests, within the Public Health England pathway. Economic models included hospital and community management of patients with suspected gastroenteritis. The model estimated costs (in 2014/15 prices) and quality-adjusted life-year losses from a NHS and Personal Social Services perspective. RESULTS: Twenty-three studies informed the review of clinical evidence (17 xTAG, four FilmArray, two xTAG and FilmArray, 0 Faecal Pathogens B). No study provided an adequate reference standard with which to compare the test accuracy of GPP with conventional tests. A meta-analysis (of 10 studies) found considerable heterogeneity; however, GPP testing produces a greater number of pathogen-positive findings than conventional testing. It is unclear whether or not these additional 'positives' are clinically important. The review identified no robust evidence to inform consequent clinical management of patients. There is considerable uncertainty about the cost-effectiveness of GPP panels used to test for suspected infectious gastroenteritis in hospital and community settings. Uncertainties in the model include length of stay, assumptions about false-positive findings and the costs of tests. Although there is potential for cost-effectiveness in both settings, key modelling assumptions need to be verified and model findings remain tentative. LIMITATIONS: No test-treat trials were retrieved. The economic model reflects one pattern of care, which will vary across the NHS. CONCLUSIONS: The systematic review and cost-effectiveness model identify uncertainties about the adoption of GPP tests within the NHS. GPP testing will generally correctly identify pathogens identified by conventional testing; however, these tests also generate considerable additional positive results of uncertain clinical importance. FUTURE WORK: An independent reference standard may not exist to evaluate alternative approaches to testing. A test-treat trial might ascertain whether or not additional GPP 'positives' are clinically important or result in overdiagnoses, whether or not earlier diagnosis leads to earlier discharge in patients and what the health consequences of earlier intervention are. Future work might also consider the public health impact of different testing treatments, as test results form the basis for public health surveillance. STUDY REGISTRATION: This study is registered as PROSPERO CRD2016033320. FUNDING: The National Institute for Health Research Health Technology Assessment programme.